Determinants of customer loyalty in the Korean smartphone market: Moderating effects of usage characteristics. Issue 4 (November 2016) - Kim, Moon-Koo; Wong, Siew Fan; Chang, Younghoon; Park, Jong-Hyun
Highlights: Smartphone attributes and corporate factors influence customer satisfaction. Customer satisfaction and switching barriers affect customer loyalty. The moderating effect of relationship length is supported. The moderating effect of usage experience is partially supported. Abstract: Since the Korean smartphone market has reached a saturation state, device manufacturing companies are re-focusing their resources and capabilities to enhance customer loyalty in order to retain existing customers and attract new customers. However, there are only few previous studies on customer loyalty of smartphones. The purposes of this study are to examine the effect of customer satisfaction and switching barriers on customer loyalty, and evaluate the moderating effects of usage characteristics in the Korean smartphone market. To test the research model, we collected data from 700 smartphone users via a face-to-face survey method. The results show that customer satisfaction and switching barriers (alternative attractiveness and switching cost) have significant impacts on customer loyalty. The device features (functions, usability, and design) and corporate factors (customer support and corporate image) significantly influence customer satisfaction. Usage characteristics (relationship length and usage experience) moderate some of the links in the research model.